L’émergence des collectivités territoriales riveraines dans la gouvernance du pas de Calais - Dover strait : une implication salutaire - Vincent Herbert (VertigO)
The Dover strait is knowwell for its High trafic density. In this context, it is seem as a major strategic Gateway, a node of international flows. On the scale of the territory, Dover strait is a maritime way, where two shores face each other : the Kent Council and the Pas-de-Calais Department, linked by maritime links and a tunnel, which should remind the remaining border between the two shores. However, a recent approach concerns initiatives for increased local communities, a memorandum of understanding, which is an important step for the joint and coordinated management of the strait. The latest actions carried out are initiative indicators of local authorities governance in the strait. The future assessment of NOSTRA project will probably confirm the need of a local management in an international shipping area.